Gut Microbiota and Diarrhea: An Updated Review - Li, Yunxia; Xia, Siting; Jiang, Xiaohan; Feng, Can; Gong, Saiming; Ma, Jie; Fang, Zhengfeng; Yin, Jie; Yin, Yulong (Frontiers in Cellular and Infection Microbiology, 2021)
Diarrhea is a common problem to the whole world and the occurrence of diarrhea is highly associated with gut microbiota, such as bacteria, fungi, and viruses. Generally, diarrheal patients or animals are characterized by gut microbiota dysbiosis and pathogen infections may lead to diarrheal phenotypes. Of relevance, reprograming gut microbiota communities by dietary probiotics or fecal bacteria transplantation are widely introduced to treat or prevent diarrhea. In this review, we discussed the influence of the gut microbiota in the infection of diarrhea pathogens, and updated the research of reshaping the gut microbiota to prevent or treat diarrhea for the past few years. Together, gut microbiota manipulation is of great significance to the prevention and treatment of diarrhea, and further insight into the function of the gut microbiota will help to discover more anti-diarrhea probiotics.